Hasil dan Risiko Portofolio Berbasis Single-Index Model Sebagai Strategi Investasi Pada Pasar Modal: Studi Saham Indeks LQ45 Bursa Efek Indonesia - Doni Teguh Wibowo; Adita Nafisa; R.M. Mahrus Alie (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
This research aims to analyze how much the return and risk level of stocks listed on index LQ45, index shares, in order to determine the portofolio optimal using a single index model, to analyze the combination of stocks included in the portofolio optimal to give return and risk portofolio.The investment decision process is a continuous decision process. This investment decision process goes on and on until the best investment decision. Stock return is income that is expressed as a percentage of the initial capital investment, profits can be in the form of return that have already or expected. Realized return is a profit that has occurred, calculated based on historical data which is also useful as a basis for determining expected profits and risk in the future. Beta is a measure of the systematic risk of a stock portofolio relative to the market risk. General, beta measures the sensitivity of the profit level of a stock against the level of profit sensitivity of a market portofolio. Beta stocks are very useful to measure how much the level of courage of investors about risk. To anticipating the risk that will be faced by investors, a method is needed to minimize the risk, while still optimizing the return to be obtained. To minimize risk and optimize the return of the investments is to diversify stocks, namely to arrange an portofolio optimal consisting of stock instruments traded on the IDX, while the method is an optimal portofolio based on a single index model, this method is calculation the stocks to help investors to determine whether a stocks can be included in the portofolio optimal and determine which stock combinations provide to optimal return. In addition to, forming a portofolio and stock combination investors are expected to make investment strategies in the capital market both active strategies or passive strategies. From the results of the analysis of the study of 45 stocks incorporated in the LQ45 index there were 37 liquid stocks from January 2017 to December 2017, obtained 14 stocks from 37 stocks formed in the portofolio optimal based on the cut off point value of 0.81883 with a return portofolio rate of 13.16 % with risk portofolio level of 0.000047%, this risk is smaller than investment in individual stocks directly. That on individual stocks the higher the risk value, the higher the level of return.